Analisis Sentimen Opini Masyarakat terhadap Pelayanan Rumah Sakit Umum Daerah menggunakan Metode Support Vector Machine dan Term Frequency - Inverse Document Frequency - Jasico Da Comoro Aruan; Bayu Rahayudi; Achmad Ridok (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Regional General Hospital is a health service institution owned by the local government. The services provided by hospitals are required to always make changes, so that the services can be in accordance with the expectations and needs of the community. Hospitals as one of the institutions that have the function of providing health services must of course be in accordance with predetermined standards. Regarding improving the quality of hospital services, the government as the main actor who plays a direct role both to be responsible and to plan, regulate, organize, foster, and supervise the implementation of improving the quality of health in this case through several public policy products has explicitly discussed and regulated everything related to achieving this. Based on the needs of hospitals in assessing public sentiment as an important point in the accreditation process of hospitals, it is necessary to analyze the sentiments of public opinion towards hospitals. To perform sentiment analysis, the method used in this research is Support Vector Machine and word weighting uses Term Frequency-Inverse Document Frequency. Testing using Cross Validation with 132 training data and 33 test data resulted in an accuracy value of 88% and recall of 87.5%, precision of 90% and f-measure of 87.5%. This value is obtained when using the parameters C=1 and Itermax=1000.